2017
DOI: 10.21767/1791-809x.1000499
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Siege Stressors, Anxiety, and Depression among Patients with Cancer in Gaza Strip

Abstract: Introduction: There is a growing body of literature examining the impact of other stressors due to daily life situation beside the stress of being diagnosed with cancer on anxiety and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…There were references to life under blockade as living in a ‘big prison’ (al sijen al wasia'a) (Bseiso & Thabet, 2017; Joma'a & Thabet, 2015), reflecting their reality that they are not free to leave the Gaza Strip, as well as symbolising feelings of punishment and entrapment. Under international law the military blockade is considered as ‘collective punishment’ (Amnesty International, 2018, p. 207).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were references to life under blockade as living in a ‘big prison’ (al sijen al wasia'a) (Bseiso & Thabet, 2017; Joma'a & Thabet, 2015), reflecting their reality that they are not free to leave the Gaza Strip, as well as symbolising feelings of punishment and entrapment. Under international law the military blockade is considered as ‘collective punishment’ (Amnesty International, 2018, p. 207).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…clean water, continuous electrical supply), and health, economic, social and educational needs (e.g. Abu‐Rmeileh et al, 2012; Bseiso & Thabet, 2017; Joma'a & Thabet, 2015; Thabet & Thabet, 2015). The blockade created feelings of being trapped and incarcerated, with 88% of Palestinian participants reporting feelings of living in a ‘big prison’ (Thabet & Thabet, 2015, p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by a descriptive-analytical study done in 2017 for cancer patients from the Gaza Strip, which indicated that they are suffering from anxiety and depression due to the siege which affects their medical condition negatively and their immune system. [35] From the experience of the second author as mental health consultant; some of the patients were reported they were being asked to work with Israeli intelligence services (spy) to get access to the health care services.…”
Section: Health Care Access DI Culties For Palestinians Living In West Bankmentioning
confidence: 99%
“…Palestinian patients faced many di culties geographically and psychologically mainly as a result of barriers to the Israeli occupation. Patients from West Bank need permission to access health care services in East Jerusalem or Gaza patients need a permit to access health care services either in East Jerusalem and West Bank need to cross barriers through Separation Wallcheckpoint too .More than ten studies and reports supported that there are negative mental health consequences of di culties in accessing health care services as a result of the Separation Wall, barriers and closures by the Israeli Authority [6][8][9] [13][15][19] [23] [30][34] These di culties are represented in the psychological burden, psychological distress, and abuse, emotional stress, negatively affect the dignity and quality of palliative care speci cally for cancer patients, and patients feel inequality, insecurity and their quality of life is affected [2][6][8][19] [28][32] [35] more seen in Gazan patients.On the other hand, there is a negative impact on the work of health-care providers, who need access to health-care places through barriers or road closures represented in psychological and moral suffering [2][9][34]. Frustration and dissatisfaction wrer reported in women needed to access health care of childbirth [21][22][26] [27] and psychological effects among children [6][19] [20].…”
Section: Health Care Access DI Culties For Palestinians Living In Wesmentioning
confidence: 99%